Deleterious effects of exposure to sodium bromate on some female mice tissues - Alothman, Sarah Ibrahim; Alzahrani, Amal Khadran; Bin Munie, Alanoud Abdulrahman; Akfah, Arwa Ali; Althobaiti, Reem Abdulshakur; Alsaeed, Samar Abdullah; Alotaibi, Shahad Mohammad; Shiaan, Sabah Jaber; Alanazi, Fatimah Musa; Alahmadi, Maram Mosleh; Alosaimi, Nojoud Muflih (Journal of medical and pharmaceutical sciences, 2019)
There are two ways, first, during the sterilization of Bro3 bromate is an anion of the element bromine has the formula of water ozone and the second addition of bromate during manufacturing, we tried through this research to shed light on the substance bromate and its risk to human health by studying the changes in some of the tissues of mice as a result of exposure to bromate by Drinking water and the use of this research (30) of female albino mice albino mice The animals were distributed in special cages with feeding bottles to drink water in a room that is ventilated subject to natural factors and provided the animal with the appropriate food. The average age of the body was 60 grams. Bromate was obtained from SATEC and the animals were divided into control groups. Five female mice were given normal drinking water. The treated group included 15 female mice were given sodium bromate at a dose. 200 mg/ kg bw in drinking water for 2 weeks after which the mice were anesthetized and dissected and liver and kidney samples were taken from female mice and kept in 10% neutral formalin solution to make tissue sections. The results showed several histological changes in the liver, such as congestion of the central vein, widening of the sinuses, the appearance of signs of death for most hepatocytes, such as cloud swelling, chromatin condensation of some nuclei, infiltration of the central vein and invasion of inflammatory cells around the central vein. With the death and decomposition of most of the tubules with tightness in the lumen of these tubules and closed some of them and expansion and infiltration in others and bleeding inside the tissue with the emergence of death and decomposition of most of the tubules cells. We conclude from this study that exposure to bromate led to a lot of damage to the liver and kidney tissue, and the kidney was more effective than the liver because the bromate pass on the kidney through the blood, which leads to the damage of kidney cells "nephrons" This proves the toxicity of the bromate of the kidney and its ability to cause Kidney failure.